Improved Efficiency and Stability of Pb/Sn Binary Perovskite Solar Cells Fabricated by Galvanic Displacement Reaction. Issue 7 (2nd January 2019) - Zhu, Zonglong; Li, Nan; Zhao, Dongbin; Wang, Liduo; Jen, Alex K.‐Y.
Abstract: Here, a simple and generally applicable method of fabricating efficient and stable Pb‐Sn binary perovskite solar cells (PVSCs) based on a galvanic displacement reaction (GDR) is demonstrated. Different from the commonly used conventional approaches to form perovskite precursor solutions by mixing metal halides and organic halides such as PbI2, SnI2, MAI, FAI, etc., together, the precursor solutions are formulated by reacting pure Pb‐based perovskite precursor solutions with fine Sn metal powders. After the ratios between Pb and Sn are optimized, high PCEs of 15.85% and 18.21% can be achieved for MAPb0.4 Sn0.6 I3 and (FAPb0.6 Sn0.4 I3 )0.85 (MAPb0.6 Sn0.4 Br3 )0.15 based PVSCs, which are the highest PCEs among all values reported to date for Pb‐Sn binary PVSCs. Moreover, the GDR perovskite‐based PVSCs exhibit significantly improved ambient and thermal stability with encapsulation, which can retain more than 90% of their initial PCEs after being stored in ambient (relative humidity (RH) ≈50%) for 1000 h or being thermal annealed at 80 °C for more than 120 h in ambient conditions. These results demonstrate the advantage of using GDR to prepare tunable bandgap binary perovskites for devices with greatly improved performance and stability. Abstract : A simple and generally applicable method to fabricate efficient and stable Pb‐Sn binary perovskite solar cells (PVSCs) based on a galvanic displacement reaction (GDR) is demonstrated. With optimizing the ratio of Pb and Sn, high PCEs of 15.85% and 18.21% are achieved for Pb‐Sn binary based PVSCs. Moreover, these Pb‐Sn based PVSCs exhibit improved stability with encapsulation.